Controlling Mechanical Machine Using PIC - Abdul-Rahman M. Nour (My University, 2007)
This project aims at developing controllers for existing machanical machines, by using Microchip PIC, the input signals and status of machine is recognised and analysed so that the correct command is sent to machine.

This project aims at developing controllers for existing machanical machines, by using Microchip PIC, the input signals and status of machine is recognised and analysed so that the correct command is sent to machine.
Controlling Mechanical Machine Using PIC